Montauk - Harrison, Nicola, 1979- (St. Martin's Press, 2019)
"Montauk, Long Island, 1938. For three months, this humble fishing village will serve as the playground for New York City's wealthy elite. Beatrice Bordeaux was looking forward to a summer of reigniting the passion between her and her husband, Harry. Instead, tasked with furthering his investment interest in Montauk as a resort destination, she learns she'll be spending twelve weeks sequestered with the high society wives at The Montauk Manor--a two-hundred room seaside hotel--while Harry pursues other interests in the city. College educated, but raised a modest country girl in Pennsylvania, Bea has never felt fully comfortable among these privileged women, whose days are devoted not to their children but to leisure activities and charities that seemingly benefit no one but themselves. She longs to be a mother herself, as well as a loving wife, but after five years of marriage she remains childless while Harry is increasingly remote and distracted. Despite lavish parties at the Manor and the Yacht Club, Bea is lost and lonely and befriends the manor's laundress whose work ethic and family life stir memories of who she once was. As she drifts further from the society women and their preoccupations and closer toward Montauk's natural beauty and community spirit, Bea finds herself drawn to a man nothing like her husband -stoic, plain spoken and enigmatic. Inspiring a strength and courage she had almost forgotten, his presence forces her to face a haunting tragedy of her past and question her future. Desperate to embrace moments of happiness, no matter how fleeting, she soon discovers that such moments may be all she has, when fates conspire to tear her world apart..."--